2015
DOI: 10.1111/jpn.12377
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary vanadium and vitamin C on egg quality and antioxidant status in laying hens

Abstract: This study assessed the effect of dietary vanadium (V) and vitamin C (VC) on production performance, egg quality and antioxidant status in laying hens. A total of 360 laying hens (31-week-old) were randomly allotted into a 3 × 3 factorial arrangement treatments (four replicates and 10 chicks per replicate) with three levels of dietary V (0, 5 and 10 mg/kg) and three levels of vitamin C (0, 50 and 100 mg/kg) for 12 weeks. The effect of V and VC did not alter egg production, egg weight, average daily feed intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
4
10
0
Order By: Relevance
“…In this study, no signi cant impact of dietary VC supplementation on laying performance and egg quality was observed, which was similar with Wang's results [25] and was different from Ahmed's results [26]. Such inconsistent results from VC supplementation was related to different oxidative stress status in laying hens, which was stronger in old layers at 75 weeks old than in young layers at 35 weeks old [8], and Hy-Line Brown layers in this study was at 40 weeks old.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, no signi cant impact of dietary VC supplementation on laying performance and egg quality was observed, which was similar with Wang's results [25] and was different from Ahmed's results [26]. Such inconsistent results from VC supplementation was related to different oxidative stress status in laying hens, which was stronger in old layers at 75 weeks old than in young layers at 35 weeks old [8], and Hy-Line Brown layers in this study was at 40 weeks old.…”
Section: Discussionsupporting
confidence: 92%
“…MDA is the end product of lipid peroxidation and is also commonly used as an indicator of lipid peroxidation. The increased levels of SOD, GSH‐PX, CAT, T‐AOC and decreased production of MDA imply an improved antioxidant status (Wang, He, et al, ). In the present study, the antioxidant activity of AMSL included in the diet was revealed by significant improvement of T‐AOC and significantly increased activities of H 2 O 2 ‐scavenging enzymes, GSH‐PX and CAT.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, very few studies investigated the interactions of vitamin C and vanadium. In one published study, vitamin C partly enhanced the serum antioxidant status and egg quality in ammonium metavanadate-intoxicated hens [80]. Some studies focused on the role of vitamin E (α-tocopherol) in the treatment of vanadium toxicity.…”
Section: Dietary Antioxidants In the Prevention Of Vanadium Toxicitymentioning
confidence: 99%